2017
DOI: 10.1002/brb3.857
|View full text |Cite
|
Sign up to set email alerts
|

NSPten knockout mice show sex‐ and age‐specific differences in ultrasonic vocalizations

Abstract: ObjectiveThe goal of this study was to identify changes in quantitative and qualitative aspects of neonatal ultrasonic vocalizations USVs in neuron‐subset specific (NS‐Pten) knockout males and females when compared with wild‐type male and female mice.BackgroundOne signaling cascade that plays a crucial role in the development of an autistic‐like phenotype is the PI3K/Akt/mTOR pathway. Mouse models that illustrate this connection include Fmr1, Tsc1, and NS‐Pten‐deficient mice. While numerous studies have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…The duration of the individual calls was also significantly shorter in crmp2 −/− pups in both P8 ( P = 0.011) and P12 ( P = 0.003) (Fig B). This early onset social behavior defects have been described in numerous mouse models of ASD with dendritic spine pathology , some of which also showed dendritic spine pathology later in adults . To broaden the analysis of crmp2 −/− social abnormalities also to the adult animals, we performed a three‐chamber sociability test.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The duration of the individual calls was also significantly shorter in crmp2 −/− pups in both P8 ( P = 0.011) and P12 ( P = 0.003) (Fig B). This early onset social behavior defects have been described in numerous mouse models of ASD with dendritic spine pathology , some of which also showed dendritic spine pathology later in adults . To broaden the analysis of crmp2 −/− social abnormalities also to the adult animals, we performed a three‐chamber sociability test.…”
Section: Resultsmentioning
confidence: 93%
“…Morphological changes were accompanied by altered social communication in early postnatal (P8 and P12) mutants and decreased sociability in adults (Fig ) further corroborating the role of CRMP2 in the pathogenesis of ASD. Defects in early postnatal USVs followed by dendritic spine pathology have been previously observed in several mouse models of ASD . The connection between early postnatal altered sociability and impairment of stereotyped axon pruning is much less clear.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have reported changes in the acoustic features like call duration, peak frequency, bandwidth, peak amplitude and call rate with age in wild-type (WT) 22 , 23 as well as in ASD models. 24 26 Furthermore, negative impact on mouse pup mother social communications was observed because of alteration in call sequences 27 which is analogous to human studies in which participants felt more negative states on listening to crying episodes of ASD babies. 23 , 28 Grimsley et al 23 studied development of vocalizations in mice and, using Zipf's statistic 29 and entropy analysis, 30 showed that sequences of syllables produced by pups were non-random.…”
Section: Introductionmentioning
confidence: 53%
“…Qualitative and quantitative analyses of USVs can help us in understanding various neurodevelopmental aspects like ethology, behavioural pharmacology, neurotoxicology, and behavioural neurogenetics. Various studies have reported changes in the acoustic features like call duration, peak frequency, bandwidth, peak amplitude and call rate with age in wild–type (WT) 22,23 as well as in ASD models 24‐26 . Furthermore, negative impact on mouse pup mother social communications was observed because of alteration in call sequences 27 which is analogous to human studies in which participants felt more negative states on listening to crying episodes of ASD babies 23,28 .…”
Section: Introductionmentioning
confidence: 85%
“…This hypothesis requires that the majority (perhaps hundreds) of individual susceptibility variants converge on sex-specific mechanisms that underpin either a female protective effect or male susceptibility effect (FPE or MSE) (27, 29). The plausibility of FPE/MSE mechanisms is supported by mouse mutants of known autism genes, which exhibit sex-specific phenotypes (7779), the presence of X-linked regulators expressed differently in males and females (80), and the influence of sex hormones such as testosterone and estrogen on normal and abnormal brain development and function (30, 31, 8183).…”
Section: Discussionmentioning
confidence: 99%